BEYOND THE MOUNTAINS: UNVEILING THE EASE OF LIVING IN THE HIMALAYAN STATE OF UTTARAKHAND IN INDIA - RAUTELA, Piyoosh; BIST, Meenakshi; BHATT, Deepshikha Rawat (Journal of Social Sciences)
This paper challenges the conventional equation of economic prosperity with human well-being and explores alternative parameters for assessing the ease of living in the Himalayan state of Uttarakhand in India. Recognizing the limitations of relying solely on economic indicators like GDP, the study examines access to basic amenities and public services across different districts of the state. Contrary to the prevailing narrative of "lack of facilities" driving out-migration from the mountainous districts, the analysis reveals that these regions may offer a comparable, if not superior, quality of life in certain aspects, particularly concerning healthcare and infant mortality rates. This finding underscores the need for a more holistic approach to development that prioritizes human well-being in its entirety, encompassing access to healthcare, education, transportation, and essential infrastructure. By examining well-being indicators beyond economic metrics, this research aims to unveil a more nuanced understanding of the ease of living in Uttarakhand and inform policy decisions that promote sustainable development, reduce out-migration pressures, and improve the quality of life for all residents, ultimately contributing to a more balanced and equitable society.